Penggunaan Media Pembelajaran Interaktif Berbasis Audio-Visual untuk Meningkatkan Kemampuan Hafalan Santri di TPA Al-Barokah Bukuan Samarinda - Masruroh, Siti; Mukiman, Nur Ayu Sitaresmi; Az-Zahra, Putri Aulia; Putri, Aprillia Nurzana Sandika; Pratiwi, Diah; Prisuminati, Devita Agus; Al-Ma’ruf, Muhammad Nizar (Faculty of Education and Teacher Training of UINSI Samarinda, 2025)
This research aims to analyze the effectiveness of using audio-visual based interactive learning media in improving the memorization abilities of students at TPA Al-Barokah Bukuan. The research method used is a qualitative method with a descriptive approach. Data was collected through observation, interviews and documentation. The research results show that audio-visual based learning media, such as animated videos of Al-Qur'an verses, audio murottals, and interactive applications, are able to increase learning motivation, simplify the memorization process, and speed up students' memory retention. This media also helps students understand the context and meaning of memorized verses, thereby improving the overall quality of memorization. However, there are several obstacles such as limited technological facilities and the need for teacher training to maximize the use of this media. This research concludes that audio-visual based learning media is an effective, innovative solution for improving students' memorization abilities, provided that there is a need for adequate support and training facilities.